Imagens de narcisos nas prateleiras do Orkut - Eler, Rogéria (2009)
The focus of this research are the technical images, analog and digital, generated, manipulated and dislocated by juvenile on the environment of the global network of computers, the Internet, where they establish new joints in what we know as subjective constructions, on the context of contemporary culture. The familiar references for socialization and identity formation get one more element, namely cyberspace, where actions and positions are gradually seized by interactors. The immersion in environments online and offline, internet pages organized and powered by four young people, contributors, in a methodological perspective of the case study, enable the perception of which images are articulated and deposited in electronic albums of sites of relationships, more specifically the orkut, what, perhaps, they wish to say or show through them, under an epistemological visual culture look. In this research, the visual culture studies, provided the basis for seeking to realize the extent, effectively, the young person, on the cyberculture context, formed from the Network, articulate their visions of the world, and how they react at the consumer market pressures. In this perspective, i highlight that interactors have relative autonomy in their actions in these environments, being formed, also, by pre- established models and under a complex system of monitoring and control even when talking with the entertainment dynamics proposed by the Network in which the photographic records and self-portraits are multiplied in line, under this approach, with the narcissistic contemporary representation.